Bekenntnis wider den Kaiser: Lucifer von Cagliari und seine Verteidigungsschrift für Athanasius - Stutz, Jonathan (Münchener theologische Zeitschrift, 2025)
Among the invective treatises against Emperor Constantius II, Lucifer of Cagliari's defense of Athanasius stands out for its distinctive use of Scripture. Drawing on passages from across the canon of the Old and New Testaments, Lucifer supports Athanasius's orthodoxy and critiques the emperor's religious policies through wide-ranging biblical quotations. Among the figures invoked in this invective, the story of Susanna, as told in the Greek version of Daniel, occupies a strategic place within the treatise. Serving as a parallel for Athanasius's own fate, the story' underscores his innocence. At the saine time, the Susanna story also provides the entry point for Lucifer to cite the Nicene Creed as testimony against the emperor's impiety.